Memoria de la trayectoria artística y pedagógica de Jaime Eduardo Duran Reyes en el ámbito de la música y la danza tradicional colombiana (2023)
As a qualitative research based on the analysis and interpretation of the artistic and pedagogical experience, this document is the result of the crossed accounts of the life story of Jaime Eduardo Durán Reyes as an artist and trainer in the field of traditional Colombian music and dance. For the development of this research, the main objective is to systematize the life experience from his trajectory and the context in which he has exercised his artistic practices and his processes as a teacher, it is theoretically supported under three categories of analysis: musical training, dance training and teaching-learning processes.